2014
DOI: 10.1186/bf03353051
|View full text |Cite
|
Sign up to set email alerts
|

Conductivity distribution and seismicity in the northeastern Japan Arc

Abstract: Wideband magnetotelluric (MT) observation data were obtained from 91 sites along six transects in the central part of the Japan Arc. Here, a quasi-3D georesistivity distribution, in addition to other geophysical and geological parameters, is used to better understand seismicity in the region. We found that high seismicity in the Central Mountain Range is due to relatively poor fluid saturation caused by volcanism. The high conductive fracture zone in the west of the Central Basin without big earthquakes is cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Many studies have shown significant correlations between electrical resistivity and seismic velocity structure, both theoretical [ Schmeling , 1986; L. MacGregor, personal communication, 2007] and empirical at a variety of scales (borehole logs [ Herwanger , 2001], cross‐hole tomography [ Herwanger et al , 2004; Saunders et al , 2005], local crustal models [ Eberhart‐Phillips et al , 1995], and crustal transects [ Fujinawa et al , 2002]). Unsworth et al [1997, 2000] and Unsworth and Bedrosian [2004] have developed a high‐resolution image of the resistivity structure near SAFOD using continuous MT profiling (Figure 7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown significant correlations between electrical resistivity and seismic velocity structure, both theoretical [ Schmeling , 1986; L. MacGregor, personal communication, 2007] and empirical at a variety of scales (borehole logs [ Herwanger , 2001], cross‐hole tomography [ Herwanger et al , 2004; Saunders et al , 2005], local crustal models [ Eberhart‐Phillips et al , 1995], and crustal transects [ Fujinawa et al , 2002]). Unsworth et al [1997, 2000] and Unsworth and Bedrosian [2004] have developed a high‐resolution image of the resistivity structure near SAFOD using continuous MT profiling (Figure 7).…”
Section: Resultsmentioning
confidence: 99%
“…MacGregor, personal communication, 2007] and empirical at a variety of scales (borehole logs [Herwanger, 2001], cross-hole tomography Figure 7. Across-fault cross sections of the geology [Bradbury et al, 2007], Vp, Vp/Vs, Qp [Bennington et al, 2008], and resistivity [Herwanger et al, 2004;Saunders et al, 2005], local crustal models , and crustal transects [Fujinawa et al, 2002]). Unsworth et al [1997Unsworth et al [ , 2000 and Unsworth and Bedrosian [2004] have developed a high-resolution image of the resistivity structure near SAFOD using continuous MT profiling (Figure 7).…”
Section: Comparing Vp Vs and Vp/vs To The Resistivity Structurementioning
confidence: 99%
“…The inclusion of even a small amount of connected melt or fluids beneath a volcano can greatly decrease the bulk resistivity of the rock mass. Although recent MT studies have investigated the two-dimensional (2D) electrical resistivity structure in several locations in northeastern Japan (e.g., [12][13][14]), the crustal magma distribution related to seismological regimes beneath Naruko volcano has not been clearly imaged yet.…”
Section: Introductionmentioning
confidence: 99%